2014
DOI: 10.1186/1471-2407-14-739
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression as risk biomarker of breast cancer metastasis: a pilot retrospective case-cohort study

Abstract: BackgroundMicroRNAs (miRNAs) are small, non-coding RNA molecules involved in post-transcriptional gene regulation and have recently been shown to play a role in cancer metastasis. In solid tumors, especially breast cancer, alterations in miRNA expression contribute to cancer pathogenesis, including metastasis. Considering the emerging role of miRNAs in metastasis, the identification of predictive markers is necessary to further the understanding of stage-specific breast cancer development. This is a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
(55 reference statements)
1
34
0
Order By: Relevance
“…29,30 Moreover, previous findings have found a direct correlation between miR-21 levels and the metastatic dissemination of human BC tumor samples. [31][32][33] Our findings revealed that Stat3 regulates ErbB-2 expression and co-opts its nuclear function to induce miR-21 and BC metastasis, highlighting Stat3 and NErbB-2 as novel targets to block metastatic dissemination in MErbB-2-positive BC.…”
Section: Introductionmentioning
confidence: 92%
“…29,30 Moreover, previous findings have found a direct correlation between miR-21 levels and the metastatic dissemination of human BC tumor samples. [31][32][33] Our findings revealed that Stat3 regulates ErbB-2 expression and co-opts its nuclear function to induce miR-21 and BC metastasis, highlighting Stat3 and NErbB-2 as novel targets to block metastatic dissemination in MErbB-2-positive BC.…”
Section: Introductionmentioning
confidence: 92%
“…The up-regulation of miR-183 is known to be associated with poor prognosis in breast cancer, colorectal cancer, hepatocellular cancer, and prostate cancer [13, 129134], while predicts a good prognosis in osteosarcoma [135] (Table 3). This finding is consistent with its functions in cell proliferation, invasion and metastasis in these tumors types.…”
Section: Resultsmentioning
confidence: 99%
“…Up‐regulation of miR‐494 has been demonstrated to be associated with tumor aggressiveness and metastasis in colorectal cancer, it was thus proposed as an independent prognostic marker for colorectal cancer patients (Sun et al., 2014). The same miRNA was also identified as a prognostic predictor for the minimal deviation adenocarcinoma (MDA) of uterine cervix (Lee et al., 2014) and as a risk biomarker for breast cancer development (Marino et al., 2014).…”
Section: Discussionmentioning
confidence: 99%